Equality of the homogeneous and the Gabor wave front set. Issue 5 (4th May 2017) - Schulz, René; Wahlberg, Patrik
ABSTRACT: We prove that Hörmander's global wave front set and Nakamura's homogeneous wave front set of a tempered distribution coincide. In addition, we construct a tempered distribution with a given wave front set, and we develop a pseudodifferential calculus adapted to Nakamura's homogeneous wave front set.